2019
DOI: 10.1016/j.scienta.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Responses of succulents to drought: Comparative analysis of four Sedum (Crassulaceae) species

Abstract: The increased frequency and intensity of drought periods is becoming a serious thread for agriculture, prompting the identification of crop species and cultivars with enhanced water stress tolerance. Drought responses were studied in four ornamental Sedum species under controlled greenhouse conditions, by withholding watering of the plants for four weeks. Determination of growth parameters (stem length, fresh weight) allowed establishing the relative degree of tolerance of the selected species as S. spurium > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 72 publications
2
25
0
1
Order By: Relevance
“…In contrast, S. acre, S. album 'Coral Carpet', S. cauticola 'Sunset Cloud', Sedum 'Czar's Gold', S. ellecombianum, S. hybridum 'Immergruchen', S. requieni, S. sexangulare, and S. spurium 'Dragon's Blood', 'John Creech', 'Pearly Pink', 'Ruby Mantle', and 'Tricolor' had high survival and vigor scores (Tables 3, 5, and 6). Our data agree with previous studies showing S. acre, S. sexangulare, and S. spurium 'John Creech' perform well on an extensive green roof, but differed in that S. cauticola, S. reflexum performed well in our study, but performed poorly in other studies (Durhman et al, 2007;Getter and Rowe, 2009;Kozminska et al, 2019). Differences in results may, in part, be related to differences in medium depth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, S. acre, S. album 'Coral Carpet', S. cauticola 'Sunset Cloud', Sedum 'Czar's Gold', S. ellecombianum, S. hybridum 'Immergruchen', S. requieni, S. sexangulare, and S. spurium 'Dragon's Blood', 'John Creech', 'Pearly Pink', 'Ruby Mantle', and 'Tricolor' had high survival and vigor scores (Tables 3, 5, and 6). Our data agree with previous studies showing S. acre, S. sexangulare, and S. spurium 'John Creech' perform well on an extensive green roof, but differed in that S. cauticola, S. reflexum performed well in our study, but performed poorly in other studies (Durhman et al, 2007;Getter and Rowe, 2009;Kozminska et al, 2019). Differences in results may, in part, be related to differences in medium depth.…”
Section: Discussionsupporting
confidence: 89%
“…Boivin et al (2001) reported Sedum survival on an extensive green roof in Quebec was limited by cold temperatures. In a more recent study, (Kozminska et al, 2019) evaluated the impact of drought on Sedum survival on a green roof; they found S. spurium and album were the most, and least drought tolerant, respectively. Interestingly, Sedum species vary in the degree they conduct C3 vs. Crassulacean acid metabolism (CAM) photosynthesis which can influence water Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in chlorophylls is a frequent response of plants to salinity and drought. Several comparative analyses of genetically related taxa have shown that the degradation of photosynthetic pigments usually correlates negatively with their relative degree of tolerance [91][92][93]. Accordingly, in this study, degradation of chlorophylls under salt stress occurred only in the least tolerant population 3 (Serp.).…”
Section: Discussionmentioning
confidence: 57%
“…In response to drought stress, drought-tolerant plants maintain water-use efficiency by reducing water loss (Anjum et al 2011) and one of such water conservation strategies in orchids is through CAM expression, which helps improve carbon gains and water use efficiency (Benzing 1998; Herrera 2009). Drought-tolerant plants may also accumulate different solutes in the cytosol to lower osmotic potential and maintain cell turgor (Jain et al 2001; Hosseini et al 2018; Kozminska et al 2018). Of these solutes, proline is the most widely studied because its accumulation is the first response of plants exposed to drought stress, with known associations in reducing photoinhibition (Anjum et al 2011).…”
Section: Introductionmentioning
confidence: 99%